Sistem Pakar Menggunakan Metode Forward Chaining Dalam Akurasi Identifikasi Penyakit Feline Urologic Sindrome - Andres Boni Fakio; Sumijan (SEULANGA SYSTEM PUBLISHER, 2021)
Cats are a type of carnivorous animal that is currently very much maintained by people. Caring for cats is very easy, but so many do not realize that when their cats fall ill, they are negligent, because they do not know about the consequences of the disease that has befallen their cats. The purpose of this study is to make it easier for users and clinics that have many patients to check and detect diseases in the cat's bladder or to determine the disease in cats by using the forward chaining method. In this study, there were 10 cases of cat patient data with fus, which data were taken from the Kih-Zima Pet Care Clinic Payakumbuh. In processing data in the form of input, determining decision tables, making rules, carrying out the tracking process, making decision trees and tracking results. The results of trials conducted with the data we get with a system that has been designed have an accuracy rate of 100% so that this designed application can be used to detect FUS in cats.